Air transport and regional development methodologies - Adler, Nicole; Niemeir, Hans-Martin; Graham, Anne 1958- (Routledge, 2021)
"Based on the comprehensive results of a four-year European Cooperation in Science and Technology (COST) Action called Air Transport and Regional Development (ATARD), Air Transport and Regional Development Methodologies promotes a better understanding of how the air transport related problems of core regions and remote regions should be addressed to enhance both economic competitiveness and social cohesion in Europe. This book discusses key methodological approaches to assessing air transport and regional development, outlining their respective strengths and weaknesses. These include input-output analysis, cost benefit analysis, computable general equilibrium models, data envelopment analysis, stochastic frontier analysis, discrete choice models and game theory. Air Transport and Regional Development Methodologies will be of interest to several large groups. Firstly, it will serve as an authoritative and comprehensive reference for academics, researchers and consultants. Secondly, it will advise policy-makers and government organizations at European, national and regional levels. Thirdly, it presents invaluable insights to transport companies such as airports and airline operators"--